2020
DOI: 10.1002/pa.2296
|View full text |Cite
|
Sign up to set email alerts
|

The role of institutional ownership structures on corporate performance

Abstract: Institutional investors are the key investors in stock markets. Stock markets are influenced by these giants. We investigate the comparative institutional ownership structure in financial and non-financial corporations. Institutional ownership structures are foreign, domestic, state, and private institutional ownership, which are examined against the corporate performance of 40 firms listed in Pakistan Stock Exchange from 2006 to 2016. Panel regression is applied to observe the results. Varied impacts for ever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
(30 reference statements)
3
2
0
Order By: Relevance
“…This indicates that institutional investors improve a company's dividend payout in order to eliminate agency conflicts and raise corporate value. According to previous studies, Tee (2019) and Hussain et al (2022) found that institutional investors positively affect corporate value, which supports the findings of the present study. The findings of this study contradict the findings of Karim & Ilyas (2021), who discovered that dividend payout and institutional investors are substitutes; hence, the beneficial effect of dividend payout on the value of the company will diminish as institutional investors increases.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This indicates that institutional investors improve a company's dividend payout in order to eliminate agency conflicts and raise corporate value. According to previous studies, Tee (2019) and Hussain et al (2022) found that institutional investors positively affect corporate value, which supports the findings of the present study. The findings of this study contradict the findings of Karim & Ilyas (2021), who discovered that dividend payout and institutional investors are substitutes; hence, the beneficial effect of dividend payout on the value of the company will diminish as institutional investors increases.…”
Section: Discussionsupporting
confidence: 92%
“…Both institutional investor types indicate that independence from institutional investors is essential to increase corporate value. The results of this study are supported by Tee (2019), who found that pressure-resistant institutional investors have a positive effect on corporate value, and Hussain et al (2022), who found that foreign institutional investors positively influence corporate value in non-financial companies.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The positive and significant findings support agency theory which states that institutional ownership with its large shares, close to perfect information, and monitoring power decreases managerial opportunism and exerts a positive influence on performance as also observed in Othmani (2022), Kyereboah-Coleman (2021), Tayachi et al (2021), Hussain et al (2022, Lev (1988), who discovered positive and significant influence of institutional ownership on financial performance. However, the study does not lend support to Jaafar and El-Shawa (2009), Sheikh et al (2013) who discovered positive and insignificant influence while Zouari and Taktak (2014) disclosed negative and insignificant effect.…”
Section: Discussion Of Resultssupporting
confidence: 78%
“…The more the board is active, the more it can play a significant role in creating harmony between the expectations of stakeholders and firm execution. Various studies ( Jabeen and Ali, 2017 ; Farooq and Manzoor, 2019 ; Usman and Alam, 2020 ; Hussain et al, 2022 ) have been done on the relationship between ownership and performance in Pakistan. They gave empirical evidence on ownership studies and asserted that ownership has become a prominent tool to gauge the performance of the firm.…”
Section: Introductionmentioning
confidence: 99%